“CARACTERIZAÇÃO DO PADRÃO DE MUTAÇÕES DA OSTEOGÊNESES IMPERFEITA E AVALIAÇÃO IN VITRO DOS EFEITOS DE ANTIOXIDANTES RESVERATROL, ÁCIDO ASCÓRBICO E CURCUMINA EM CÉLULAS-TRONCO MESENQUIMAIS” - Trancozo, Maira (2022)
Osteogenesis Imperfecta (OI) is an inherited disorder of connective tissues that contain collagen in their formation. More than 20 OI-related genes have been reported in the last years. Most cases happen due mutations inherited with autossomic dominant in